Surgical treatment of acute appendicitis with laparoscopic technologies - R. Zh. Izbassarov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The aim of the work was to study the effectiveness of the Computer Assisted Surgical Intervention in 597 patients with the diagnosis of acute appendicitis. The use of the Computer Assisted Surgery technology allowed in all cases to refine the diagnosis, tovisualize the shape and location of the appendix, the presence of peritonitis, and the possibility of an adequate minimally invasive surgery. This greatly reduced the diagnostic phase, frequency of complications, and postoperative hospital period